Brain Plasticity in Blind Subjects Centralizes Beyond the Modal Cortices - Ortiz-Terán, Laura; Ortiz, Tomás; Perez, David L.; Aragón, Jose Ignacio; Diez, Ibai; Pascual-Leone, Alvaro; Sepulcre, Jorge (Frontiers in Systems Neuroscience, 2016)
It is well established that the human brain reorganizes following sensory deprivations. In blind individuals, visual processing regions including the lateral occipital cortex are activated by auditory and tactile stimuli as demonstrated by neurophysiological and neuroimaging investigations. The mechanisms for such plasticity remain unclear, but shifts in connectivity across existing neural networks appear to play a critical role. The majority of research efforts to date have focused on neuroplastic changes within visual unimodal regions, however we hypothesized that neuroplastic alterations may also occur in brain networks beyond the visual cortices including involvement of multimodal integration regions and heteromodal cortices. In this study, two recently developed graph-theory based functional connectivity analyses, interconnector analyses and local and distant connectivity, were applied to investigate functional reorganization in regional and distributed neural-systems in late-onset and congenitally blind cohorts each compared to their own group of sighted controls. While functional network alterations as measured by the degree of differential links occurred in sensory cortices, neuroplastic changes were most prominent within multimodal and association cortices. Subjects with late-onset blindness showed enhanced multimodal integration connections in the parieto-opercular, temporoparietal junction and ventral premotor regions, while congenitally blind individuals exhibited increased superior parietal cortex connections. This study reveals the critical role of recipient multi-sensory integration areas in network reorganization and cross-modal plasticity in blind individuals. These findings suggest that aspects of cross-modal neuroplasticity and adaptive sensory-motor and auditory functions may potentially occur through reorganization in multimodal integration regions.